2013
DOI: 10.1209/0295-5075/102/67009
|View full text |Cite
|
Sign up to set email alerts
|

Half-metallicity in a \chem{BiFeO_3/La_{\frac{2}{3}}Sr_{\frac{1}{3}}MnO_3} superlattice: A first-principles study

Abstract: PACS 73.20.-r -Electron states at surfaces and interfaces PACS 75.70.-i -Magnetic properties of thin films, surfaces, and interfaces PACS 78.20.-e -Optical properties of bulk materials and thin films Abstract -We present first-principles results for the electronic, magnetic, and optical properties of the BiFeO3/La 2 3 Sr 1 3 MnO3 heterostructure as obtained by spin-polarized calculations using density functional theory. The electronic states of the heterostructure are compared to those of the bulk compounds. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 47 publications
4
13
0
Order By: Relevance
“…The energetically favorable configuration after the structural optimization, see Figure 1c, is LaO-terminated with interfacial O atoms located on top of interfacial Fe atoms and has sep W =-5.13 eV. This is consistent with the previous findings for the supercell consisting of LSMO and rhombohedral BFO 18,22 and is also in a similar LSMO/YMnO 3 system, 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 -9 -1c) is 1.56 Å. More specifically, the O atoms are shifted out of the cationic plane, see Therefore, the BFO is subjected to a reduced ferroelectric polarization.…”
Section:  Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The energetically favorable configuration after the structural optimization, see Figure 1c, is LaO-terminated with interfacial O atoms located on top of interfacial Fe atoms and has sep W =-5.13 eV. This is consistent with the previous findings for the supercell consisting of LSMO and rhombohedral BFO 18,22 and is also in a similar LSMO/YMnO 3 system, 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 -9 -1c) is 1.56 Å. More specifically, the O atoms are shifted out of the cationic plane, see Therefore, the BFO is subjected to a reduced ferroelectric polarization.…”
Section:  Results and Discussionsupporting
confidence: 91%
“…17 Jilili et al have found that the LSMO/rhombohedral BFO superlattice maintains the half-metallic character of bulk LSMO. 18 Moreover, Guo et al have discovered that the anomalies in the temperature-dependent ferromagnetic resonance spectra of LSMO occur at the transition temperature of Fe polarization, indicating a strong interfacial coupling between Fe and Mn. 19 Yu et al have reported a significant exchange bias for the coupling between LSMO and rhombohedral BFO using the X-ray circular dichroism method.…”
mentioning
confidence: 99%
“…5 So far, the LSMO/R-BFO bilayers have been a topic of much interest and debate. [6][7][8] X-ray magnetic circular dichroism measurements have demonstrated a significant exchange bias for the coupling between them mediated by an interfacial magnetic state, 9 and it is supposed to have different origins of the interfacial Fe ferromagnetic ordering like strong Mn-Fe hybridization, 9 Fe-O-Fe bond angle alteration and suppression of octahedral tiltings near the interface, 10 charge and orbital ordering, 11 and Fe/Mn intermixing. 12 The magnitude of induced Fe magnetization is proved to be sensitive to the size of the band gap of BFO.…”
Section: Introductionmentioning
confidence: 99%
“…Aimed at investigating the interfacial magnetic order of BFO, all of four models contain the FeO 2 terminations. For LSMO, we focus on the LaO terminations first, which are the most stable interfacial configuration both in LSMO/BFO and LSMO/YMnO 3 heterostructures as calculated previously. , We further build the MnO 2 terminations, which contain opposite interfacial I and II layers with respect to LaO terminations. Two opposite directions of ferroelectric polarizations in BFO are analyzed in the two terminations, respectively, as shown in Figure .…”
Section: Calculation Details and Modelsmentioning
confidence: 99%